The Influence of Digital Game-Based Learning and Students' Learning Motivation Upon the Students' English Learning Achievement in SMPN 10 Samarinda - Syamwardana, Muhammad Ibnu; Soe’oed, Rahmat; Teodora, Maria (Syntax Corporation, 2025)
This research explores the impact of digital game-based learning and students' learning motivation on English learning achievement in SMPN 10 Samarinda. The three main objectives of this study are to determine the influence of digital game-based learning on students' learning achievement, the influence of learning motivation on students' learning achievement, and the combined influence of digital game-based learning and learning motivation on students' learning achievement. This study employs a mixed-methods research design, utilizing questionnaires administered to 187 students who have undergone digital game-based learning. Additionally, semi-structured interviews with two students provide supplementary data regarding the impact of digital game-based learning. The subjects for the study were selected through stratified purposive random sampling. The research has undergone several processes to ensure data reliability, including validation and reliability tests, classical assumption tests, and hypothesis testing. The study offers insights into how digital games can influence students' learning achievement, particularly in the English language, and provides valuable input for the development of well-integrated learning designs tailored to the English as a foreign language setting. Moreover, the findings have practical implications for enhancing the utilization of digital games in education and developing more effective learning strategies in the English as a foreign language context. It was found that, based on t-test results with a p-value of 0.111, students did not experience a significant impact from the use of digital games, and interviews revealed dissatisfaction and boredom due to overly simplistic and repetitive questions.